Everything is figureoutable - Forleo, Marie (Portfolio/Penguin, 2019)
"Let's be honest--none of us were given an owner's manual at birth. If you're having trouble solving a problem or making a dream happen, the problem isn't you. It's not that you're not hardworking, intelligent or deserving, but that you haven't yet installed the one key belief that will change everything. My mom, who has the tenacity of a bulldog and curses like a truck driver, explained it to me this way, "Nothing in life is that complicated. You can do whatever you set your mind to if you just roll up your sleeves, get in there, and do it. Everything is figureoutable." Whether you want to leave a dead end job, break an addiction, learn to dance, heal a relationship, grow a business, master your money, travel the globe, or solve world hunger, Everything is Figureoutable will train your brain to think more creatively and positively--especially in the face of setbacks. Inside, you'll learn: The simple practice that makes it 42% more likely you'll achieve your goals. How to overcome a lack of time and money. How to find two free hours a day. What to do if you're multipassionate and want to follow all your dreams. How to deal with criticism, haters, and imposter syndrome. How to tell the difference between fear and intuition. A fail-proof test to make the right decisions, especially in high-stakes situations. You'll also hear triumphant stories of everyday people confronting loss, illness, and heart-wrenching pain. Like the 23-year-old single mom with no education past 10th grade who used the Everything is Figureoutable philosophy to get her GED and then her bachelor's degree, and now she's in law school. I wrote this book because, if I got hit by a bus tomorrow, it's the one idea I'd want to leave behind. When I'm having a rough time or when a shitstorm comes to town, Everything is Figureoutable instantly turns things around. It's more than just a fun phrase to say. It's a philosophy of relentless optimism. A mindset. A mantra. A conviction. Most important, it's about to make you unstoppable"--